Effect Exposure of Mobile Phone Radiation on Blood Parameters in Rats - Al Abas, Marwa Ali Abd; AL-Hakkak , Zaid Makki Mohammed (Iraqi Journal of Science, 2021)
The aim of the research was to assess effects of short and long-period exposure to radiation from mobile phone on blood indices in experimental rats. In this study forty mature female rats were used; the animals were divided into two experimental group, each group consists of twenty animals. Short-period group of rats were exposed to cell phone radiation for different duration 30 m, 60 m, and 90 m per day for six weeks. Long-period group of rats were exposed to radiation from mobile phone for different duration 2h, 4h, and 6h per day for three months. The study noticed that there was significant (P≥0.05) elevation in total white blood cells and the study demonstrated significant increment (P≥0.05) in percentage of lymphocytes (71.1%) of rats which exposed to radiation from mobile phone for short-period in (90 minutes) compared to the control group (42.64%). While, the study revealed that there was a significantly (P≥0.05) lower percentage of neutrophils (15.36%) in rats that were exposed to mobile phone radiation for long-period in (6 hours) compared with the control group (52.12%).The study recorded that there was a significant (P≥0.05) elevation in total red blood corpuscles and packed cell volume of rats exposed to radiation from mobile phone for short and long-period in different times compared with control. On the other hand, the research indicated that there was a significant (p≤0.05) decrement in mean corpuscles volume (MCV), mean corpuscle hemoglobin (MCH), mean corpuscle hemoglobin concentration and red blood cell distribution width standard deviation (RDW-SD) of rats to radiation from mobile phone for short and long-period in different times than control group.